PENGARUH PROFITABILITAS, REPUTASI KANTOR AKUNTAN PUBLIK, FINANCIAL DISTRESS TERHADAP AUDIT DELAY (Studi Pada Perusahaan Sub Sektor Property dan Real Estate di Bursa Efek Indonesia) - Mileinia Sukoco Putri; Moh. Amin; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
The purpose of this study was to determine the effect of Profitability, Reputation of Public Accounting Firms, Financial Distress on Audit Delay in Property and Real Estate sub-sector companies. The population in this study is the Property and Real Estate sub-sector companies listed on the Indonesia Stock Exchange for the period 2018-2021 using the purposive sampling method. The test result in this study indicate that profitability, Reputation of Public Accounting Firms, Financial Distress simultaneously affect the Audit Delay. Partial testing of the Profitability variable has a negative effect on Audit Delay. Partial testing of the Public Accounting Firm Reputation variable has no effect on Audit Delay. Partial testing of the Financial Distress variable has no effect on Audit Delay.Keywords: Profitability, Reputation of Public Accounting Firms, Financial Distress, Audit Delay